Factors Influencing Nurses In The Implementation Of Integrated Management For Sick Children (MTBS) At Mongeudong Health Center, Banda Sakti District Lhokseumawe City - Muammar, Muammar (Sean Institute, 2024)
In Indonesia, the under-five mortality rate is still a significant public health problem, although there has been a decline in the last few decades. Data from the Ministry of Health of the Republic of Indonesia shows that under-five deaths are often caused by diseases such as pneumonia, diarrhea, malaria and malnutrition. This requires the implementation of MTBS at the basic health service level, especially at Community Health Centers and Posyandu, to provide early intervention and appropriate treatment to toddlers. This study aims to determine the factors that influence nurses in implementing Integrated Management of Sick Toddlers. The population in this study were all nurses on duty at the Mongeudong Community Health Center, namely 35 people with a sampling technique using the total population. This research is analytical with a cross sectional design with data processing methods using Editing, Coding, Tabulating and Entry. Based on the research, it was found that the majority of respondents implemented MTBS, namely 54.3%, the frequency of respondents' education was high education, namely 40.0%, the frequency of information obtained by respondents was sufficient information, namely 60.0%, the frequency of respondents' training was attending training, namely 57.1%. The results of the analysis of the influence of nurse education in implementing Integrated Management of Sick Toddlers obtained a value of ρ value = 0.003 (P < 0.05), analysis of the influence of information in implementing MTBS obtained ρ value = 0.019 (P < 0.05), the influence of training in implementing MTBS obtained ρ value = 0.005 which means there is a significant relationship between MTBS implementation and education, information and training. It is hoped that all nurses at the Mongeudong Health Center can increase their knowledge about implementing MTBS.